Ciudad de Caballococha - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Vista del puerto del pueblo de Caballococha ubicado en el distrito de Ramón Castilla y a su vez de la provincia de Mariscal Ramón Castilla en el departamento de Loreto.
ENGLISH: View of the port of the town of Caballococha located in the district of Ramón Castilla and in turn of the province of Mariscal Ramón Castilla in the department of Loreto.

SPANISH: Vista del puerto del pueblo de Caballococha ubicado en el distrito de Ramón Castilla y a su vez de la provincia de Mariscal Ramón Castilla en el departamento de Loreto.
ENGLISH: View of the port of the town of Caballococha located in the district of Ramón Castilla and in turn of the province of Mariscal Ramón Castilla in the department of Loreto.
Caballococha City
Keywords: Iquitos (Perú)|~|Architecture|~|Rural|~|Amazon|~|Nature|~|Jungles|~|Paisajes|~|Iquitos (Perú)|~|Iquitos (Perú)|~|arquitectura|~|rural|~|naturaleza|~|junglas